From Mozambique to Brazil: a biome of resistance: From Mozambique to Brazil: a biome of resistance (Élisée - Revista de Geografia da UEG, 2021)
In this paper we explore how the African oral tradition crossed the ocean and continued life, developing political, medical, cultural, etc. As a form of knowledge, it operates in Mozambique and Brazil, specifically in territories taken over by savanna and Cerrado. From two different, yet converging personalities and their narratives, we explore voices from the Cerrado and savanna, masters of knowledge who use the word as the raw material of their work and have the African oral tradition as their memory and library, available to their community. The meeting point of knowledge in these highlighted territories is the ancestry that is understood here as an organizing and structuring category of the African worldview, but it is also an element of construction that crosses the time-space capable of being noticeable in social dynamics.
Keywords: Cerrado. Savanna. Ancestrality. Oral tradition. Knowledge.